2016
DOI: 10.1371/journal.pone.0148104
|View full text |Cite
|
Sign up to set email alerts
|

Liver Toxicity of Current Antiretroviral Regimens in HIV-Infected Patients with Chronic Viral Hepatitis in a Real-Life Setting: The HEPAVIR SEG-HEP Cohort

Abstract: ObjectiveTo assess the current frequency of ART-associated grade 3–4 transaminase elevations (TE) and grade 4 total bilirubin elevations (TBE) in HIV-infected patients with chronic hepatitis B and/or C, who start a new regimen of ART.Patients and MethodsA total of 192 pre-treated or treatment-naive HIV infected patients with HBV and/or HCV-coinfection who started ART in eight Southern Spanish centers from July/2011-December/2013, were followed for 12 months in this prospective study.ResultsForty-one (21.4%) su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 35 publications
(38 reference statements)
1
13
0
Order By: Relevance
“…This retrospective cohort study was conducted on HIV-positive individuals with an initially normal hepatic function and without HBV/HCV infection. We found that liver damage (grade II–IV LEE/TBE) occurred in all patients at different period of ART, indicating that hepatic damage always exists among HIV/AIDS patients receiving ART, which has been shown in a few previous studies,4 5 although the incidence rate of LEE/TBE in our study was quite stable and low in the longer ART during times. Our study showed that the liver damage prevalence was 12.41% (263/2119) (figure 1), which is lower than those (14%–23%) in several previous studies conducted on HIV/AIDS patients 21 22.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…This retrospective cohort study was conducted on HIV-positive individuals with an initially normal hepatic function and without HBV/HCV infection. We found that liver damage (grade II–IV LEE/TBE) occurred in all patients at different period of ART, indicating that hepatic damage always exists among HIV/AIDS patients receiving ART, which has been shown in a few previous studies,4 5 although the incidence rate of LEE/TBE in our study was quite stable and low in the longer ART during times. Our study showed that the liver damage prevalence was 12.41% (263/2119) (figure 1), which is lower than those (14%–23%) in several previous studies conducted on HIV/AIDS patients 21 22.…”
Section: Discussionsupporting
confidence: 71%
“…Hepatitis viral infections, either hepatitis B virus (HBV) or hepatitis C virus (HCV), have been reported to lead to hepatotoxicity 12 13. Elevated hepatotoxicity was observed to be associated with ART in HIV/AIDS patients co-infected with HBV or HCV 4 12. ART-related hepatotoxicity was also reported in quite a few previous studies 6 11 13.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations